Resistance mechanisms of epidermal growth factor receptor tyrosine kinase inhibitors in non‐small cell lung cancer patients: A meta‐analysis - Kobayashi, Nobuaki (Thorac Cancer, 2021)
BACKGROUND: Differences in the resistance mechanisms of epidermal growth factor receptor tyrosine kinase inhibitors in patients with non‐small cell lung cancer (NSCLC) harboring epidermal growth factor receptor mutations are unknown. This meta‐analysis aimed to clarify the differences in resistance mechanisms after treatment with various epidermal growth factor receptor tyrosine kinase inhibitors. METHODS: We systematically searched PubMed, Cochrane, and Web of Science on July 29, 2020, for relevant studies on acquired resistance mechanisms against epidermal growth factor receptor tyrosine kinase inhibitors. The primary outcome measure was differences in the resistance mechanism between individual or generations of epidermal growth factor receptor tyrosine kinase inhibitors. RESULTS: In total, 33 trials involving 2418 individuals were included and analyzed. T790M was significantly less frequent after afatinib treatment (40.2%, 95% confidence interval [CI]: 31.7%–48.7%) than after gefitinib and erlotinib treatments (52.5%, 95% CI: 48.7%–56.3%, p = 0.005). There were no significant differences between Asian and non‐Asian patients in the incidence of T790M after gefitinib, erlotinib, and afatinib treatments. Regarding epidermal growth factor receptor pathway‐independent resistant mechanisms, the incidences of small cell lung cancer transformation (osimertinib: 7.9%, 95% CI: 3.6%–12.2%, others: 2.3%, 95% CI: 0.8%–3.8%) and Kirsten rat sarcoma (KRAS) viral oncogene homolog mutation (osimertinib: 4.6%, 95% CI: 1.5%–7.7%, others: 0.2%, 95% CI: 0.0%–1.7%) were significantly higher following osimertinib treatment than with others. CONCLUSIONS: Significant differences in the incidence of resistance mechanisms among epidermal growth factor receptor tyrosine kinase inhibitors exist, which should be taken into consideration when choosing the treatment strategy.